Family Conflict as A Social Dynamic: An Analysis of Conflict Theory In The Perspective of Islamic Family Law - azzam, Muazzam Khairi; Hamim, Khairul; Indrawati Purnamasari, Teti (STAINI Press, 2026)
Conflict is an inseparable part of social dynamics. From a sociological perspective, conflict theory asserts that society is not a harmonious entity, but rather an arena of conflicting interests rife with inequality. Conflict is an inherent phenomenon in social life. Conflict theory, as an important perspective in sociology, emphasizes that society is not a harmonious space, but rather an arena of conflicting interests rife with inequality. This article aims to outline the nature of conflict theory, its basic assumptions, the key figures who developed it, and its relevance and critique in the contemporary social context. Using a literature review approach, this article provides a comprehensive overview of conflict as a social phenomenon that is not solely destructive but can also serve as a trigger for change and societal transformation. Furthermore, this study highlights the relevance of conflict theory from the perspective of Islamic family law. Several important issues such as polygamy, divorce, and inheritance distribution often give rise to tensions between classical Islamic jurisprudence norms and modern demands for gender equality. Thus, conflict theory can be an analytical instrument that helps understand the dynamics of social tensions as well as the legal challenges within contemporary Muslim families.